The Role of Glutathione in Treating Pathological Changes Caused by Exposure to Phthalates in Some Tissues of Female Mice (The International Journal for Scientific Research, 2025)
Phthalates (PAEs) are the most widely used Polyvinyl chloride (PVC) plasticizers. They are produced with a global production of 470 million pounds. It is extensively used in many consumer products such as cosmetics, toys, bottles, food packaging, medical plastic devices, building and construction. It has become a serious problem in recent years. PAEs can be introduced particularly by dermal absorption, ingestion and air inhalation. Laboratory animal studies have reported the endocrine disrupting effects of PAEs and have been recognized as substances of high concern due to their property of reaching animals tissues and inducing a negative impact on health. Our current study involved oral injection of Potassium Hydrogen Phthalate and Glutathione as an antioxidant daily for 3 weeks to investigate the adverse effects of phthalate on the organ tissues (Ovary, liver and kidney) and improving tissue damage resulting from phthalates using the antioxidant glutathione in female Swiss mice. The results revealed organs damage associated with impaired oxidative stress and histopathological changes such as intravenous bleeding, cell destruction, chromatin condensation and apoptosis in all organs. Treatment with glutathione restricts PAE negative impacts and showed histological improvements such as reappearance of organ’s cells and minimized bleeding in all tested organs.
Keywords: Endocrine disruptors; Phthalates; Oxidative Stress; Antioxidants; Glutathione; Apoptosis; Congestion